Localized Forms of Parametric Vibrations of a Cylindrical Shell Laying on a Non-Homogeneous Elastic Foundation - G.I. Mihasev (Механика машин, механизмов и материалов, 2008)
The problem on the parametric vibrations of a thin, long cylindrical shell lying on an elastic foundation under action of compressive static axial forces and pulsing pressure is considered. Under an assumption that a thickness and physical characteristics of the shell as well as a foundation factor of an elastic basis are functions of a longitudinal coordinate, solutions of the Flugge type equations are constructed in the form of functions decaying far from some parallel on the shell surface.